2015
DOI: 10.1187/cbe.14-08-0132
|View full text |Cite
|
Sign up to set email alerts
|

Use of Feedback-Oriented Online Exercises to Help Physiology Students Construct Well-Organized Answers to Short-Answer Questions

Abstract: Online feedback-oriented exercises were developed to help undergraduate physiology students practice formulating answers to short-answer questions. Student feedback regarding the learning value of these assignments and the ability of these assignments to improve student outcomes when answering short-answer questions on summative examinations were assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…The provision of regularly-spaced formative examinations to these students prior to their summative exams may also have allowed them to be well prepared for assessment. Having opportunities to practice retrieving information pertaining to course content when studying is an active study approach that has been suggested to promote learning and long-term retention more effectively than passive processes such as reading the textbook and course notes (Carnegie, 2015;Karpicke, Butler, & Roediger III, 2009;Orr & Foster, 2013;Roediger & Karpicke, 2006). That being said, correct answer position and the possible development of a pattern could become important when a student does not know the correct answer and has resorted to guessing (Attali & Bar-Hillel, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The provision of regularly-spaced formative examinations to these students prior to their summative exams may also have allowed them to be well prepared for assessment. Having opportunities to practice retrieving information pertaining to course content when studying is an active study approach that has been suggested to promote learning and long-term retention more effectively than passive processes such as reading the textbook and course notes (Carnegie, 2015;Karpicke, Butler, & Roediger III, 2009;Orr & Foster, 2013;Roediger & Karpicke, 2006). That being said, correct answer position and the possible development of a pattern could become important when a student does not know the correct answer and has resorted to guessing (Attali & Bar-Hillel, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Frequent homework can be an opportunity to give students that practice. Studies suggest that assigning homework in college biology classes can increase performance ( Lefcort and Eiger, 2003 ; Orr and Foster, 2013 ; Carnegie, 2015 ). Indeed, frequent, active homework that consists of writing or problem solving is an important part of the high or moderate course structure that has been shown to reduce achievement gaps for students from underrepresented groups and to improve learning for all students ( Freeman et al.…”
Section: How Common Teaching Techniques May Affect the Neurobiology Omentioning
confidence: 99%
“…The testing effect has been applied to classroom contexts across the disciplines of psychology (Leeming, 2002; Trumbo et al , 2016), statistics (Lyle and Crawford, 2011), medicine (Larsen et al , 2009; Messineo et al , 2015), and biology (Orr and Foster, 2013; Carnegie, 2015). In an introductory biology classroom, Orr and Foster (2013) studied the use of low-stakes (10% of course grade) quizzes and found that students who participated in 100% of the available quizzes scored better on course exams than students who participated in 0% of the quizzes.…”
Section: Introductionmentioning
confidence: 99%